Analysis of Determinants of Capital Structure of Plantation Companies in Indonesia (Case Study Public Listed Plantation Companies Q1 2006 - Q4 2012) - Sakinah, Alida Nur; Anggono, Achmad Herlanto (Journal of Business and Management, 2014)
Abstract- This research focuses on capital structure with the objective to examine the effect of several determinants of capital structure of listed plantation companies in Indonesia. The factors influencing capital structure analyzed in this research are asset tangibility, growth, firm size, and profitability. The research is conducted by observing financial data of 10 listed plantation companies in Indonesia from period 2006 the earliest to 2012 the latest. Panel data regression technique is used in this research and random effects assumption is chosen as the best to be applied on the capital structure determinants model, and so the model is constructed by using Generalized Least Square method. The capital structure determinants model constructed in this research shows that asset tangibility and growth of the firm (represented by asset growth) do not have significant effect on debt to equity ratio. It is most likely that these two aspects are not taken into account by listed plantation companies in Indonesia in making their capital structure decision. However, firm size (represented by natural logarithm of total asset) and profitability (with net profit margin as proxy) are proven to have significant negative effect on capital structure. If firm size increases by 10%, debt to equity ratio will decrease by 1.42%; and if profitability increases by 10%, debt to equity ratio will decrease by 4.87%. From the result of this research, it can be concluded that only firm size and profitability that have significant relationship with capital structure for the case of listed plantation companies in Indonesia. These aspects thus should be put into consideration by management and investor or other concerned party when assessing capital structure policy of the companies. Keywords: Capital Structure, Plantation Companies, Asset Tangibility, Growth, Firm Size, Profitability, Panel Data Regression